1986
DOI: 10.1089/aid.1.1986.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Immune Dysfunction in Rabbits Associated With Chronic Administration of Enemas and Rectal Insemination

Abstract: NZ rabbits were treated with various combinations of enemas and intrarectal insemination (1 or 3 ml of semen a week) to investigate the effects of intestinal uptake and immunogenicity of seminal components and of an unrelated antigen, bovine serum albumin (BSA), given simultaneously. For 5 months the treatment was limited to enemas and/or semen, and total immunoglobulins and antisperm and antilymphocyte antibodies were determined. Then, without interruption of the treatments, the animals received two courses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although it is questionable whether deterioration of the immune system is the cause or consequence of infection with the human immunodeficiency virus, it is undisputable that homosexual men are the most affected by the disease (17,29). Results of previous experimental studies suggested that long-term colonic lavages (43,44) and intrarectal (i.r.) insemination (31,44,45) may selectively predispose the host to immunosuppression.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is questionable whether deterioration of the immune system is the cause or consequence of infection with the human immunodeficiency virus, it is undisputable that homosexual men are the most affected by the disease (17,29). Results of previous experimental studies suggested that long-term colonic lavages (43,44) and intrarectal (i.r.) insemination (31,44,45) may selectively predispose the host to immunosuppression.…”
mentioning
confidence: 99%
“…Results of previous experimental studies suggested that long-term colonic lavages (43,44) and intrarectal (i.r.) insemination (31,44,45) may selectively predispose the host to immunosuppression. Chronic colonic lavages promoted an increase in the humoral response to soluble (seminal fluid and bovine serum albumin) and particulate (spermatozoa and sonicated sheep erythrocytes) antigens and the production of immune complexes (43)(44)(45).…”
mentioning
confidence: 99%
See 1 more Smart Citation